Optical excitation of zigzag carbon nanotubes with photons guided in nanofibers - Broadfoot, S; Dorner, U; Jaksch, D (2012)
We consider the excitation of electrons in semiconducting carbon nanotubes by photons from the evanescent field created by a subwavelength-diameter optical fiber. The strongly changing evanescent field of such nanofibers requires dropping the dipole approximation. We show that this leads to novel effects, especially a high dependence of the photon absorption on the relative orientation and geometry of the nanotube-nanofiber setup in the optical and near-infrared domain. In particular, we calculate photon absorption probabilities for a straight nanotube and nanofiber depending on their relative angle. Nanotubes orthogonal to the fiber are found to perform much better than parallel nanotubes when they are short. As the nanotube gets longer the absorption of parallel nanotubes is found to exceed the orthogonal nanotubes and approach 100% for extremely long nanotubes. In addition, we show that if the nanotube is wrapped around the fiber in an appropriate way the absorption is enhanced. We find that optical and near-infrared photons could be converted to excitations with efficiencies that may exceed 90%. This may provide opportunities for future photodetectors and we discuss possible setups. © 2012 American Physical Society.